1821 - 2021: A Feminist Revolution - Demetriou, Demetra (Byzantion Nea Hellás, 2023)
This article examines the reception of the 200th anniversary of the Greek War of Independence in contemporary women’s writing. It offers an analysis of a wide range of female writers, which demonstrates a major literary tendance concerning the manifestation of a feminist or gendered consciousness, which the critic and historian of Modern Greek literature can no longer ignore. In the contemporary context, the event of the Greek Revolution is received through a more private prism, which in the works of female writers relates to the female experience, visibility, and identity. These works denounce in particular the exclusion of the female experience of the Revolution from dominant national narratives or defy the male authority of the literary canon with respect to the poetry of Dionysios Solomos, whom the writers in question however respect and creatively rework. All in all, this study demonstrates the necessity for a contemporary feminist criticism with solid methodological foundations.